Does Reproductive Success in Orchids Affect the Evolution of Their Number of Flowers? - Iva Traxmandlová; Michaela Steffelová; Pavel Kindlmann (Plants)
Species are disappearing worldwide, and changes in climate and land use are commonly assumed to be the most important causes. Organisms are counteracting the negative effects of environmental factors on their survival by evolving various defence strategies, which positively affect their fitness. Here, the question addressed is: can evolution shape these defence strategies so that they positively affect the fitness of an organism? This question is complex and depends on the taxa and environmental factors. Therefore, here, only a special case of this question is studied in deceptive species of orchids: reproductive success (RS, ratio of the number of fruits to the number of flowers produced by a plant during the whole season), a commonly used measure of fitness is used to develop a model describing how RS affects the number of flowers, n, of a plant. This model predicts that: (i) the resulting relationship between RS and n is a positively skewed parabola, (ii) the distribution of the numbers of individuals with a specific number (n) of flowers, NI(n), also resembles a parabola and is also positively skewed, and that (iii) the peak of the distribution of NI is to the left of the peak of RS. A large set of data is presented that supports these predictions. If the data set is small, the concave positively skewed parabolic RS–n dependence is obscured by other factors.